2023
DOI: 10.3390/molecules28145595
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effect and Mechanism of Chitooligosaccharides Were Revealed Based on Lipidomics in Diet-Induced Obese Mice

Abstract: Chitooligosaccharide (COS) is a natural product from the ocean, and while many studies have reported its important role in metabolic diseases, no study has systematically elaborated the anti-obesity effect and mechanism of COS. Herein, COSM (MW ≤ 3000 Da) was administered to diet-induced obese mice by oral gavage once daily for eight weeks. The results show that COSM administration reduced body weight; slowed weight gain; reduced serum Glu, insulin, NEFA, TC, TG, and LDL-C levels; increased serum HSL and HDL-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Certain drugs used in the clinical treatment of obesity are associated with adverse effects, including nausea, insomnia, constipation, gastrointestinal problems, and potential cardiovascular complications [ 34 ]. Therefore, numerous initiatives are underway to explore and cultivate anti-obesity foods and food ingredients that can effectively reduce body fat accumulation, decrease the risk of obesity-related chronic diseases, and reduce potential side effects associated with clinical treatments [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain drugs used in the clinical treatment of obesity are associated with adverse effects, including nausea, insomnia, constipation, gastrointestinal problems, and potential cardiovascular complications [ 34 ]. Therefore, numerous initiatives are underway to explore and cultivate anti-obesity foods and food ingredients that can effectively reduce body fat accumulation, decrease the risk of obesity-related chronic diseases, and reduce potential side effects associated with clinical treatments [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The collected mice blood was added to 2.0 mL sterile Eppendorf (EP) tubes, and the serum was allowed to stand for 1 h at room temperature until significant stratification of the blood can be observed and then centrifuged in a centrifuge at 4 °C (3000 rpm, 15 min) to obtain a supernatant serum sample ( Zhou et al, 2023 ). The results of serum ALT, AST, ALP, LDH, TNF-α, IL-1β, IL-6, TG, TC, HDL-C, LDL-C and VLDL were determined by appropriate kits.…”
Section: Methodsmentioning
confidence: 99%
“…These microorganisms play a crucial role in shaping the diversity and composition of gut microbiota, which in turn affect the host’s digestive, metabolic, and immune antioxidant abilities. The typical microecologics include probiotics, prebiotics, synbiotics and postbiotics [ 22 , 23 ]. Numerous studies have reported therapeutic effects of microecologics on chronic diseases through restoration of gastrointestinal function [ 24 , 25 ], immunity [ 26 ], improvement in energy utilization and overall metabolism [ 27 ].…”
Section: Microecologicsmentioning
confidence: 99%